Implementation of Concepts and Thoughts on Sharia in DSKS (Dewan Syariah Kota Surakarta) - Ruwandi Susanto; Qoree Butlam; Mohamed Akhiruddin Ibrahim; Muthoifin (Walidem Institute and Publishing (WIP), 2023)
The purpose of the study is to find out the concept of sharia and its implementation in the city of Surakarta perspective of M. Muinudinillah's Thought at the Sharia Council of Surakarta City (DSKS). M. Muinudinillah Basri Expressing His Thoughts and Ideas about Sharia He founded the Tahfizul Qur'an Islamic Boarding School (PPTQ) Ibnu Abbas Klaten, Lecturer at the University of Muhammadiyah Surakarta and as chairman at the Sharia Council of Surakarta City. Even the works of M. Muinudinillah Basri's thoughts on Sharia are contained in many books, journals and articles. In addition to his works, he is known as Ustadz, Ulama, Intellectual, Lecturer, Activist and Unifier of ukhuwah. This research uses qualitative studies with library research methods. The approach used is historical and descriptive which aims to describe, describe clearly following what is happening in the actual reality of the object of study studied. The results of this study show that M. Muinudinillah Basri's thoughts on Sharia are very relevant to what was applied by M. Muinudinillah Basri.